Biomanufacturing process for the production of bacteriocins from Bacillaceae family - Lajis, Ahmad Firdaus (SpringerOpen, 2020)
Members of Bacillaceae family are of major interest in medical industry due to vast antimicrobial peptides they produce as therapeutic agents. For decades, synthetic and natural occurring antibiotics have been used to treat infectious diseases, but heavy dependence on these drugs has led to significant drawbacks which propel continuous development of new antibiotics generation. Recent findings have shown several bacteriocins of Bacillaceae as promising alternatives to the conventional drugs to combat the emergence of new drug-resistant pathogens. In this present review, Bacillaceae bacteriocins’ classification such as lantibiotics and thiazole/oxazole-modified microcins as well as their biochemical characterization such as sensitivity to enzymes, temperature, pH and chemicals are described. This article enlightens on the medical application of several Bacillaceae bacteriocins emphasizing those that underwent and on-going preclinical trials. This review also discusses the development of Bacillaceae bacteriocins production, focusing strains selection and fermentation factors such as inocula size, medium (carbon, nitrogen, minerals sources), temperature, pH, agitation and aeration rate, dissolved oxygen tension (DOT), fermentation time, inducers and mode of operation via various statistical methods for their optimization. It also highlights recent advance in the production of bioengineered and recombinant bacteriocins in bioreactors system which are rarely disclosed in literature.